Resources of Innovation Uniqueness - Al-Musawi, Hawraa Ibrahim Jasim; Salih Hussein, Wasan (Al-Adab Journal, 2021)
This research discusses the resources of innovation uniqueness as some poets ae unique in some personal features which make them as the most active in bring the innovative meaning .Also the motives of the personal attitudes that the poet confront becomes active in emergence of implicit innovation in his inspiration .This research is divided into two axis .The first axes discusses : The personal fascination that is materialized in precise thinking inspiration and deformity .The second ax4es : The motive of personal attitude that the poet thus the emergences of innovative poets is resulted .